EVALUASI PELAYANAN JAMINAN KESEHATAN MELALUI MOBILE JKN DI POLI GIGI RUMAH SAKIT HAJI MEDAN TAHUN 2022 - Sri Lestari Ramadhani Nasution; Ahmad Affandi; Ermi Girsang (Postgraduate, University of Mataram, 2023)
Health service is a concrete form of public service. Mobile JKN is an application made by BPJS Health to make it easier for participants to obtain services. The aim of the research is to evaluate health insurance services through mobile JKN at the Dental Clinic of Haj Hospital Medan in 2022. The research method is qualitative and quantitative design (Mix Methode). The research was conducted at the Dental Polyclinic at Haji Hospital Medan in May 2023. A qualitative research sample of 10 participants came to dental polo, a quantitative sample of 100 respondents came to dental polo. Collecting data with questionnaires and in-depth interviews. The results of the study, the majority of respondents who came to the dental polyclinic were aged 36-45 years (late adulthood) totaling 26 respondents (26%), health insurance services through mobile JKN are not good enough (20-55) as many as 55 respondents (55%). Participants who haven't used mobile JKN don't even know about mobile, don't know the convenience with mobile JKN, don't know the benefits of mobile JKN, participants are not interested in using mobile JKN because they haven't received education about mobile JKN. Participants who use mobile JKN assume that the JKN car program is an application that is used to register for health services without having to come to the hospital, the JKN mobile application simplifies and reduces queues at the hospital so that participants also assume that mobile JKN helps in health services, using mobile JKN makes it easier and saves time as well as efficiently and effectively.